ジッケン ヨウ ナンキョク ホーバークラフト ノ ウンヨウ ト ヒョウカ - 村尾, 麟一; ムラオ, リンイチ; 竹内, 貞男; タケウチ, サダオ; 稲葉, 稔; イナバ, ミノル; 細谷, 昌之; ホソヤ, マサユキ; Murao, Rinichi; Takeuchi, Sadao; Inaba, Minoru; Hosaya, Masayuki (1994)
P(論文) 本報告では, 実験用南極ホーバークラフトの昭和基地における8年間の運用と経験が記述されている。南極における輸送・交通手段としてのホーバークラフトの有用性を調査し, 実用ホーバークラフト建造の技術データを得るために試作された2.8t実験用ホーバークラフトが1981年1月に昭和基地近くに揚陸され, 1990年2月まで性能, 操縦性, 環境適応性, 駐機・保管・整備に関する評価試験が行われた。その結果, 気象・地形に関する南極特有の環境下で運行・駐機・保管・整備上の艇の能力と限界が評価された。ホーバークラフト運用信頼性に影響する主要な気象環境因子はエンジンに対する雪の吸い込みであって, エアフィルター・ラジエータに付着し出力低下と温度上昇をもたらす。地形環境的には基地と海氷域の間に発生するタイドクラックの乗り越しに最も人手を要した。操縦試験の結果艇は摩擦の小さい氷上走行時に操舵応答に敏感で習熟に時間を要することが判明したので操縦特性の解明のためシミュレーションモデルを開発した。これらの経験に基づいて昭和基地付近の夏期の生物観測・氷状偵察・沿岸調査等観測支援活動に対する運用に適当なホーバークラフト機体・保管整備の仕様が提案されている。 In this report are reviewed the operating procedures and test results of an experimental hovercraft that was tested during 8 years at Japan's Syowa Station Antarctica. A small size-2.8t-experimental hovercraft was unloaded near Syowa Station in January 1981 and left there for testing of performance, maneuverability and maintenance requirements until it was decommissioned in February 1990. The dominant environmental feature affecting reliable hovercraft operation was ingestion of snow into the engine. The ingestion of cooling air had to be restricted because snow clogged the air filters and blocked the engine radiator. To cross a tide crack, the crack had to be filled with snow before the craft was towed by a snow vehicle. This situation interfered with the simple operation and maintenance of the experimental hovercraft. A test program was carried out to evaluate the maneuverability of this craft. It was found that the yaw response of this craft was very sensitive under certain ice conditions. Digital simulation of motion was attempted to understand the craft's response to steering. The operation of the experimental hovercraft was evaluated from the viewpoint of support and survey for scientists' activities in the Antarctic. For this purpose, specifications of a hovercraft, parking and storage that are feasible at Syowa Station are proposed. departmental bulletin paper